A low volume flexible CPW‐fed elliptical‐ring with split‐triangular patch dual‐band antenna. Issue 8 (5th April 2019) - Dattatreya, Gopi; Naik, Ketavath K.
Abstract: In this article, the intensive investigations are carried out on a low volume compact flexible antenna for wireless applications with a novel structure model. The proposed model has considered as an elliptical‐ring with split‐triangular patch (ERSTP) antenna with the coplanar waveguide feeding to achieve dual‐bands. The ERSTP antenna is designed with polyimide material having the volume ( L a  ×  W a  ×  h ) 99 mm 3 . The ERSTP antenna resonates with 2.60 GHz and 3.48 GHz frequencies with a reflection coefficient of −21.92 dB and −32.14 dB and a gain of 2.39 dBi and 1.75, dBi respectively. The impedance bandwidths are 100 MHz and 330 MHz observed at two frequency bands. The proposed ERSTP antenna has operated on mobile‐worldwide interoperability for microwave access (M‐WiMAX) and worldwide interoperability for microwave access (WiMAX) bands respectively. The simulated and measured results of ERSTP antenna are in good agreement.